Relationship between sleep efficacy endpoints and measures of functional status and health‐related quality of life in participants with narcolepsy or obstructive sleep apnea treated for excessive daytime sleepiness. (13th October 2020) - Weaver, Terri E.; Mathias, Susan D.; Crosby, Ross D.; Bron, Morgan; Bujanover, Shay; Menno, Diane; Villa, Kathleen F.; Drake, Christopher
Abstract: This study examined the correlation between improvements in excessive daytime sleepiness in participants with obstructive sleep apnea or narcolepsy and changes in functional status, work productivity and health‐related quality of life. Data from two 12‐week randomized controlled trials of solriamfetol were analyzed. Participants completed the Epworth Sleepiness Scale, 10‐item Functional Outcomes of Sleep Questionnaire, Work Productivity and Activity Impairment questionnaire and 36‐Item Short Form Health Survey and performed the Maintenance of Wakefulness Test at baseline and weeks 4, 8 and 12. Patient Global Impression of Change was assessed at weeks 4, 8 and 12. Pearson correlations were calculated for change in scores from baseline to week 12. For both studies, changes in the 10‐item Functional Outcomes of Sleep Questionnaire were highly correlated (absolute value >0.5) with changes in Epworth Sleepiness Scale scores; changes in multiple domain scores of the 36‐Item Short Form Health Survey and Work Productivity and Activity Impairment questionnaire were moderately correlated (0.3–0.5) with changes in Epworth Sleepiness Scale scores in both studies and highly correlated for participants with narcolepsy. Changes in Maintenance of Wakefulness Test scores correlated moderately with changes in Epworth Sleepiness Scale scores in both studies. At week 12, Patient Global Impression of Change ratings correlated highly with Epworth Sleepiness Scale and 10‐item Functional Outcomes of Sleep Questionnaire scores for both disorders. Other correlations were low. Self‐reported assessments of sleepiness and global improvement appear to be more strongly correlated with measures of functioning and health‐related quality of life than objectively assessed sleepiness.